Development of an Android Application to Identify Fish Species Using Kotlin-based Android Studio - Sampurna, Adam Mulya; ., Alfani; Setiawan, Ade; Al Kautsar, Hanggoro Aji (Universitas Bina Sarana Informatika, 2025)
Indonesia has a rich variety of fish species, but the understanding and knowledge of the public about these fish species is still limited. This is the background of the problem raised in this research, with the aim of providing education to the Indonesian people about the types of fish in Indonesia. The solution offered is the development of an Android application that can identify fish species in Indonesia. This application is expected to be an effective educational tool for the community. The methods used in the development of this application include collecting data documentation from the internet, literature studies from various research journals, literature, and other scientific articles. The collected data is then used as a basis for application development. Tools used in the development of this application include Android Studio as the main software, Firebase as a database, Kotlin as a programming language, and XML as a markup language for data storage and transmission. Figma is used to design the application interface. Application testing is carried out using the black box testing method to ensure application functionality runs well. The algorithm used in this application is a recursive algorithm for processing fish identification data. With this application, it is hoped that Indonesian people can more easily recognize and understand the types of fish that exist in Indonesia, so that they can reduce the number of fish species in Indonesia.